2012
DOI: 10.1016/j.urology.2011.10.042
|View full text |Cite
|
Sign up to set email alerts
|

Are Multiple Cryoprobes Additive or Synergistic in Renal Cryotherapy?

Abstract: OBJECTIVE To investigate the relationship between multiple cryoprobes was investigated to determine whether they work in an additive or synergistic fashion in an in vivo animal model because 1.47 mm (17-gauge) cryoprobes have been introduced to the armamentarium for renal cryotherapy. METHODS Laparoscopic-guided percutaneous cryoablation was performed in both renal poles of 3 pigs using 3 IceRod cryoprobes. These 12 cryolesions were compared with 12 cryolesions using a single IceRod cryoprobe. Each cycle con… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
10
0

Year Published

2014
2014
2024
2024

Publication Types

Select...
5
1
1

Relationship

0
7

Authors

Journals

citations
Cited by 16 publications
(10 citation statements)
references
References 25 publications
0
10
0
Order By: Relevance
“…21 Young et al confirmed this finding, concluding that the ice ball volumes increased in size more than expected when pulses were used in tandem, demonstrating that cryolesions that are created by multiple simultaneous 1.47-mm probes have a synergistic effect. 22…”
Section: Literature Reviewmentioning
confidence: 99%
“…21 Young et al confirmed this finding, concluding that the ice ball volumes increased in size more than expected when pulses were used in tandem, demonstrating that cryolesions that are created by multiple simultaneous 1.47-mm probes have a synergistic effect. 22…”
Section: Literature Reviewmentioning
confidence: 99%
“…Unfortunately, limited information is available on the expected ice ball size for multiple probes, and for nonstandard ablation times. In multiple-probe ablation, there is a variable amount of synergy between the probes, which can result in a larger ablation zone than expected [12; 13]. …”
Section: Introductionmentioning
confidence: 99%
“…However, accurate simulations are too slow for routine clinical use, and simple ice ball models are inaccurate due to synergy between probes [12]. …”
Section: Introductionmentioning
confidence: 99%
“…Currently, commercial systems are nearly non existent, and emerging tools are limited to a visualization of the isotherms obtained for each needle in ideal conditions (usually in a gel). They do not account for any influence of the soft tissue properties, the presence of blood vessels, or the combined effect of multiple needles highlighted in [Young et al 2012]. As a consequence, large safety margins over 5 mm are defined, as detailed in [Georgiades et al 2012].…”
Section: Introductionmentioning
confidence: 99%